A new species of Hisonotus (Siluriformes: Otothyrinae) from the upper rio Paraná and rio São Francisco basins, Brazil - Roxo, Fábio F. [UNESP]; Silva, Gabriel S.C. [UNESP]; Waltz, Brandon T.; Melo, Jorge E.G. (Magnolia Press, 2016)
A new species of Hisonotus is described from the upper rio Paraná and rio São Francisco basins. The new species is distinguished from congeners by (1) completely exposed abdomen with no development of dermal plates (with the exception of extremely small platelets present near the urogenital pore in some specimens) and the combination of the following characters: (2) lack of a conspicuous tuft of enlarged odontodes on posterior tip of parieto-supraoccipital; (3) rectangular dorsal-fin spinelet; (4) complete mid-lateral plate series; (5) higher number of vertebrae, 29-30; (6) dark brown coloration on caudal fin with one pair of circular hyaline colored regions at center of both lobes; (7) absence of broad light stripes on dorsolateral surface of head; (8) odontodes not forming longitudinally aligned rows on head and trunk; and (9) apex of teeth yellowish in color.
Keywords: Cascudinhos; Catfishes; Ichthyology; Neotropical fishes; Taxonomy